THE IMPACT OF OWNERSHIP STRUCTURE ON INTELLECTUAL CAPITAL PERFORMANCE (ICP); AN EMPIRICAL ANALYSIS IN PAKISTAN STOCK EXCHANGE - Fahad Mujahid; Laila Taskeen Qazi (International Journal of Contemporary Issues in Social Sciences, 2024)
The aim of this research is to explain the effect of Value added Intellectual Capital (VAICTM) and its components that is Value added Human capital (VAHC), Structural capital Value added (SCVA) and Value added capital employed (VACA) on the ownership percentage of different types of owners. To explain the hypothesized relationship different set of independent variables are used. The data of 140 listed companies from Pakistan Stock Exchange for a time period spanning over 6 years from 2017 to 2022 is used for analysis. The results concluded that VAICTM only showed a positive significant relation with Individual ownership and with the remaining components of ownership structures that includes ownership by largest shareholder (ownership concentration), ownership by state, ownership by companies and ownership by institutions it showed an insignificant relation.